Green-emitting Gd2O2S:Tb3+ and red-emitting Y3Al5O12:Cr3+ phosphors: a suitable selection for enhancing color quality of remote phosphor structure - Nguyen Thi Phuong Loan; Thinh Cong Tran (Universitas Ahmad Dahlan, 2020)
This article demonstrates green-emitting phosphor Gd2O2S:Tb3+ and red-emitting phosphor Y3Al5O12:Cr3+ application in the triple-layer phosphor WLED to enhance optical performance. The arrangement of phosphor layers in the WLED is red phosphor Y3Al5O12:Cr3+ on top, green phosphor Gd2O2S:Tb3+ in the middle, and yellow phosphor YAG:Ce3+ at the bottom. The principal to utilize these phosphor materials is the exploitation of additional red light component and green light component from the green and red phosphor to enrich the color rendering index (CRI) and luminous efficacy. The influences of green phosphor and red phosphor are also estimated with a new quality indicator, the color quality index (CQS). The results show red phosphor Y3Al5O12:Cr3+ enable CRI when its concentration increases while green phosphor exhibits a contrast reaction. Regarding the CQS, the optimal red phosphor concentration for CQS is from 10% to 14%, disregard the concentration in green phosphor. The improvement that applying these two phosphor materials brought comes from limiting the light loss from back-scattering and strengthen chromatic performance through addition red and green light components. These findings can support manufacturers in adapting to modern lighting requirements by improving CRI, CQS and particularly luminous efficiency to more than 40%.